An assessment of risk posed by a Campylobacter-positive puppy living in an Australian residential aged-care facility - Moffatt, Cameron; Appuhamy, Ranil; Andrew, Will; Wynn, Sandy; Roberts, Jan; Kennedy, Karina (Western Pacific Surveillance and Response, 2014)
Introduction: In April and June 2012, two outbreaks of Campylobacter gastroenteritis were investigated in an Australian aged-care facility (ACF); a Campylobacter-positive puppy was identified as a potential source of infection. Methods: An expert panel was convened to assess transmission risk from the puppy to elderly residents and to guide further public health action. Criteria considered as part of the panel’s assessment included the puppy’s infectivity, the bacterium’s transmissibility, puppy–resident contact, infection control and cleaning practices and animal management at the facility. A literature review was used to assist the panel, with a final risk being determined using a likelihood and consequence matrix. Results: The panel determined that the setting and low infective dose made transmission likely despite varying degrees of contact between the puppy and cases. While infection control practices were generally appropriate, the facility’s animal policy did not adequately address potential zoonotic risk. Conclusion: In summary, puppies should not be considered as companion animals in ACFs due to high rates of Campylobacter carriage and the underlying susceptibility of the elderly. Infection control and animal policies in ACFs should reflect an awareness of zoonotic disease potential.